Being Isolated and Protected Is Better Than Just Being Isolated: A Case Study From the Alacranes Reef, Mexico - Favoretto, Fabio; Mascareñas-Osorio, Ismael; León-Deniz, Lorena; González-Salas, Carlos; Pérez-España, Horacio; Rivera-Higueras, Mariana; Ruiz-Zárate, Miguel-Ángel; Vega-Zepeda, Alejandro; Villegas-Hernández, Harold; Aburto-Oropeza, Octavio (Frontiers in Marine Science, 2020)
Isolated reefs suffered from overfishing to a lesser extent than coastal reefs systems. Nevertheless, the exploitation of coastal areas forced fishers to move offshore to compensate for their decreasing catches, helped by an overall increase in their technological capabilities. Thus, these once pristine isolated areas are under increasing threat and should be considered a protection priority. Here, we compared the fish and epibenthic community of two isolated coral reefs in the southern Gulf of Mexico: one is the Alacranes reefs a Marine Protected Area (MPA) with two No-Take Zones (NTZs) and the other is Bajos del Norte an Open Area (OA). Alacranes reef is ~135 km off the northern coast of the Yucatan Peninsula while Bajos del Norte ~160 km. Our results show that despite being isolated, the OA reefs never reach the same biomass levels of MPA or NTZ reefs which in some cases exceeded 1 ton/ha. Furthermore, 70% of the reefs within NTZ and MPA had a large predatory fish (e.g. sharks, jackfish, groupers) biomass relative contribution larger than 25%, while only two reefs in the OA had a relative piscivore contribution of more than 25%. Large predatory fish have a larger contribution to overall biomass within NTZs than MPAs reefs, even at low biomass values, suggesting that NTZ is more effective in protecting large predators. NTZ and MPA reefs also showed from 5 to 10% higher coral cover than OA which had a higher erect algae cover (~22.9%). Indicating that the disruption of the trophic pyramid caused by the fishing pressure in OA reefs is reflecting on the trophic cascades controlling the benthic communities balance. These isolated areas represent the last pillars of natural diversity and are under such an increasing anthropogenic pressure that just being isolated is not enough anymore to guarantee a safe zone from detrimental activities like overfishing. Immediate establishment of protective NTZ is needed to maintain the role they play as a natural wilderness capital.